FAIR Game Design Framework: A Player-Centered Model for Developing and Evaluating Digital Games - Kirginas, Sotiris (Bina Nusantara University, 2026)
This paper introduces the FAIR Game Design Framework, a player-centered model that emphasizes Freedom, Autonomy, Immersion, and Replayability. While previous frameworks have addressed isolated aspects of player experience—such as motivation, flow, or usability—a noticeable gap remains in integrating these key dimensions into a single, cohesive model that captures the holistic nature of gameplay. To bridge this gap, we present both the theoretical foundations of the FAIR framework and a practical evaluation tool designed to operationalize its principles in real-world settings. The four pillars of the framework reflect fundamental qualities that contemporary players increasingly value. Freedom highlights the importance of meaningful choices and open-ended possibilities; Autonomy stresses a sense of control and ownership over decisions; Immersion captures the depth of engagement and narrative absorption; and Replayability ensures sustained interest and long-term value. Together, these components create a balanced structure that can guide design decisions across genres and platforms. We demonstrate the framework’s versatility through case studies of contemporary games, showing how it can be applied to assess design strengths, identify areas for improvement, and compare player experiences across titles. Ultimately, the FAIR model offers a dual contribution: for developers, it acts as a practical guide to designing richer, more engaging experiences; for researchers, it provides an evaluative metric that enables systematic study of player-centered game design. By uniting theoretical insight with practical application, the framework advances the discourse on what makes games compelling and sustainable.